Ruthenium complex with benznidazole and nitric oxide as a new candidate for the treatment of chagas disease. - Renata Sesti-Costa; Zumira A Carneiro; Maria C Silva; Maíta Santos; Grace K Silva; Cristiane Milanezi; Roberto S da Silva; João S Silva (Public Library of Science (PLoS), 2014)
Chagas disease remains a serious medical and social problem in Latin America and is an emerging concern in nonendemic countries as a result of population movement, transfusion of infected blood or organs and congenital transmission. The current treatment of infected patients is unsatisfactory due to strain-specific drug resistance and the side effects of the current medications. For this reason, the discovery of safer and more effective chemotherapy is mandatory for the successful treatment and future eradication of Chagas disease.We investigated the effect of a ruthenium complex with benznidazole and nitric oxide (RuBzNO2) against Trypanosoma cruzi both in vitro and in vivo. Our results demonstrated that RuBzNO2 was more effective than the same concentrations of benznidazole (Bz) in eliminating both the extracellular trypomastigote and the intracellular amastigote forms of the parasite, with no cytotoxic effect in mouse cells. In vivo treatment with the compound improved the survival of infected mice, inhibiting heart damage more efficiently than Bz alone. Accordingly, tissue inflammation and parasitism was significantly diminished after treatment with RuBzNO2 in a more effective manner than that with the same concentrations of Bz.The complexation of Bz with ruthenium and nitric oxide (RuBzNO2) increases its effectiveness against T. cruzi and enables treatment with lower concentrations of the compound, which may reduce the side effects of Bz. Our findings provide a new potential candidate for the treatment of Chagas disease.